Physical Preparation in Female Rugby Codes: An Investigation of Current Practices - Omar Heyward; Omar Heyward; Ben Nicholson; Stacey Emmonds; Stacey Emmonds; Gregory Roe; Gregory Roe; Ben Jones; Ben Jones; Ben Jones; Ben Jones; Ben Jones (Frontiers Media S.A., 2020)
Female sports have recently seen a dramatic rise in participation and professionalism world-wide. Despite progress, the infrastructure and general sport science provisions in many female sports are behind their male counterparts. From a performance perspective, marked differences in physical and physiological characteristics can be seen between the sexes. Although physical preparation practices for male athletes are known, there are currently no published literature pertaining exclusively to female athletes. This information would provide invaluable data for both the researcher and practitioner alike. This survey therefore aimed to examine current practices utilized in female rugby codes (union, league, and sevens). A questionnaire assessing seasonal physical preparation practices, recovery, monitoring and sport science technology, and unique aspects in female rugby was developed. Thirty-seven physical preparation practitioners (32 males, 5 females) responded to the questionnaire. Most participants (78%) worked with national or regional/state level female athletes. Performance testing was more frequently assessed in the pre- (97%) and in-season (86%), than off-season (23%). Resistance, cardiovascular, sprint and plyometric training, and recovery sessions were all believed to be important to enhancing performance and implemented by most participants (≥ 89%). Sport science technologies were commonly (54%) utilized to inform current practice. Menstrual cycle phase was monitored by 22% of practitioners. The most frequently reported unique considerations in female rugby codes included psycho-social aspects (41%), the menstrual cycle (22%), and physical differences (22%). Practitioners working with female rugby can use the presented data to inform and develop current practices.